2021
DOI: 10.1088/1742-6596/1730/1/012141
|View full text |Cite
|
Sign up to set email alerts
|

On transient heat analysis of a two-step convective reactive cylinder

Abstract: This article looks at the analysis of heat transfer due to combustion of reactive materials in a stockpile modelled in a cylindrical domain. The transient heat analysis is studied through the investigation of effects kinetic parameters, embedded on the differential equation governing the problem, have on the temperature of the system. The temperature patterns due to the parameters effect, are depicted in graphs generated through Maple software. The complicated nonlinear partial differential equation is solved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The influence of density variation with temperature is approximated following Boussinesque approximation. The equations governing the momentum and energy balance under the assumptions above are as follows [14][15][16]20,26]:…”
Section: Mathematical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of density variation with temperature is approximated following Boussinesque approximation. The equations governing the momentum and energy balance under the assumptions above are as follows [14][15][16]20,26]:…”
Section: Mathematical Analysismentioning
confidence: 99%
“…In addition, enhancement in the chemical reaction rate leads to increased heat generation in the stockpile, resulting in quick auto-ignition. Lebelo et al [14][15][16] examined the two-step thermal decomposition of combustible materials in a sphere. They identified that elevation in the two-step kinetic parameter diminishes the rate of heat loss on the sphere's surface, which, in turn, speeds up auto-ignition.…”
Section: Introductionmentioning
confidence: 99%